Analisis Perbandingan Campuran Aditif Etilen Glikol 30 banding 70 dan 50 banding 50 Pada Cairan Sistem Pendingin Toyota New Rush 1.5 MT - Candra, Riki; Rofiroh, Rofiroh (Motor Bakar : Jurnal Teknik Mesin, 2023)
A vehicle engine is a system that works simultaneously, which during operation can cause an increase in temperature due to the operation of an engine. Ethylon glycol is an additive used as a medium in cooling systems. When using coolants, ethylene glycol is often mixed with distilled water to obtain effective heat absorption results in the radiator. With an ethylene glycol composition of 30 to 70, namely a mixture of 30% ethylene glycol and 70% distilled water, and an ethyl glycol composition of 50 to 50, namely a mixture of 50% ethylene glycol and 50% distilled water for radiator use in the 2019 Toyota new Rush 1.5 MT. This test aims to obtain a comparison of the temperature values resulting from heat dissipation in the radiator between the two types of coolant composition. Tests carried out with rotations of 800, 1600, 2400 and 3200 RPM obtained results from using 30/70 colant, namely an average working temperature of 94.3oC and from using 50/50 colant, namely an average working temperature of 92.8oC. The use of LLC 30/70 coolant is 1.72% hotter than SLLC 50/50 coolant..